Orthodontic Approach to Obstructive Sleep Apnea Syndrome Cases - Handan Tuğçe Oğuz; Neslihan Üçüncü (Turkish journal of orthodontics, 2005)
Sleep apnea syndrome is a disease which occurs during sleeping and which is characterized by apneic and hypopneic events, low oxygen levels in lungs (hypoxia), blood oxygen desaturation, sleep arousal and/or awakening. The syndrome has three types; central, mixed and obstructive. Central and mixed apnea can be treated only by medical practitioners but in the treatment of obstructive sleep apnea orthodontists and maxillofacial surgeons have an important role. The aim of this review is showing the role and importance of orthodontists in the treatment of obstructive sleep apnea.